2020
DOI: 10.1534/g3.120.401500
|View full text |Cite
|
Sign up to set email alerts
|

Maize Introgression Library Provides Evidence for the Involvement ofliguleless1in Resistance to Northern Leaf Blight

Abstract: Plant disease resistance is largely governed by complex genetic architecture. In maize, few disease resistance loci have been characterized. Near-isogenic lines are a powerful genetic tool to dissect quantitative trait loci. We analyzed an introgression library of maize (Zea mays) near-isogenic lines, termed a nested near-isogenic line library for resistance to northern leaf blight caused by the fungal pathogen Setosphaeria turcica. The population was comprised of 412 BC5F4 near-isogenic lines that originated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 73 publications
(168 reference statements)
2
22
0
Order By: Relevance
“…Near‐isogenic lines (NILs) have been used extensively to characterize, validate and dissect QTL in maize (Szalma et al , 2007; Pea et al , 2009; Chung et al , 2010; Eichten et al , 2011; Mideros et al , 2014; Peiffer et al , 2014; Benson et al , 2015; Lennon et al , 2016, 2017; Xiao et al , 2016; Kolkman et al , 2019; Martins et al , 2019). However, the development of NILs is time‐consuming and costly, as it requires several generations of backcrossing, selfing and genotyping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Near‐isogenic lines (NILs) have been used extensively to characterize, validate and dissect QTL in maize (Szalma et al , 2007; Pea et al , 2009; Chung et al , 2010; Eichten et al , 2011; Mideros et al , 2014; Peiffer et al , 2014; Benson et al , 2015; Lennon et al , 2016, 2017; Xiao et al , 2016; Kolkman et al , 2019; Martins et al , 2019). However, the development of NILs is time‐consuming and costly, as it requires several generations of backcrossing, selfing and genotyping.…”
Section: Introductionmentioning
confidence: 99%
“…Via the International Maize and Wheat Improvement Center (CIMMYT), Syngenta AG (Basel, Switzerland) has made public a large panel of maize NILs derived from crosses between 25 diverse inbred lines and B73, henceforth referred to as the Syngenta panel (Gandhi et al , 2008). Kolkman et al (2019) recently used a subset of 412 ‘nested’ NILs (nNILs) from the Syngenta panel, which were chosen for having introgressions surrounding disease resistance QTL, for GWA and candidate gene identification of resistance to northern leaf blight (NLB).…”
Section: Introductionmentioning
confidence: 99%
“…However, many more genes behind the QTLs must be characterized (Martins et al, 2019) and additional breeding schemes must be developed and/or existing ones adapted (Wisser et al, 2006) in order to find a suitable way through the “jungle” of uncharacterized QTLs. One strategy is the development of an introgression library combined with high density marker coverage to resolve QTLs (Kolkman et al, 2020).…”
Section: Leaf Disease Resistance Breeding Approachesmentioning
confidence: 99%
“…One strategy is the development of an introgression library combined with high density marker coverage to resolve QTLs (Kolkman et al, 2020).…”
Section: Le Af D Is E a S E Re S Is Tan Ce B Reed Ing A Pproache Smentioning
confidence: 99%
“…A major QTL was identified for AUDPC on chromosome 8 between the bins 8.05–8.06 in F 2:3 populations studied for NCLB resistance 53 . Recently, a study conducted on a nested near isogenic line library for resistance to NCLB, also identified NILs with introgressions across centromeric region of chromosome 8 (bin 8.05), which overlaps two major genes ht2 and htn 54 . The fact that one of our mapping panels also identified a strongly associated set of closely located SNPs in this important chromosomal bin, indicated possible presence of a quantitatively expressed major gene or dQTL in this region present in the genetic background of the maize lines of this particular panel.…”
Section: Discussionmentioning
confidence: 99%